2015
DOI: 10.1016/j.rehab.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

User-centred design in brain–computer interface research and development

Abstract: In a recent article [1], Nijboer addressed an important topic for brain-computer interface (BCI) research and development: How can we develop a technology that will in the end be used by the target population? [1]. We have few recent studies demonstrating the independent home use of BCI [2][3][4]. Although these were single case studies, they do show the potential feasibility of BCI for the target population and provide valuable information on the prerequisites for transferring BCI to patients' homes and for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This stands in opposition to studies that found that user's traits can modulate the user's BCI experience (see section "2.1 Human factors related to BCI engineering and ergonomics"). In this case, both past and current research suggest a strong correlation between the user's self-reported operation performance and their self-reported performance satisfaction with their BCI performance (see for a discussion Kübler et al, 2015). In addition, the user's self-reported and perceived effectiveness (Kübler et al, 2014) and their acceptability of the BCIs as well as their affinity with technology (e.g., Hagedorn et al, 2021;Leeuwis et al, 2021) seem to modulate BCI performance among different vulnerable end-user groups.…”
Section: User Traits and Bci Performance: The Role Of Personality Traitsmentioning
confidence: 82%
See 1 more Smart Citation
“…This stands in opposition to studies that found that user's traits can modulate the user's BCI experience (see section "2.1 Human factors related to BCI engineering and ergonomics"). In this case, both past and current research suggest a strong correlation between the user's self-reported operation performance and their self-reported performance satisfaction with their BCI performance (see for a discussion Kübler et al, 2015). In addition, the user's self-reported and perceived effectiveness (Kübler et al, 2014) and their acceptability of the BCIs as well as their affinity with technology (e.g., Hagedorn et al, 2021;Leeuwis et al, 2021) seem to modulate BCI performance among different vulnerable end-user groups.…”
Section: User Traits and Bci Performance: The Role Of Personality Traitsmentioning
confidence: 82%
“…This has encouraged discussions about the relevance of research on human factors not only in the domain of human-computer interaction (HCI) in general, but in the domain of BCI research, its deployment and application as well (for an overview see for example, Botte-Lecocq et al, 2014;Kleih and Kübler, 2015). Furthermore, the discussion on the role of the BCI user has promoted theoretical suggestions of how to integrate human factors into BCI technology by means of a user-centered approach (for an overview see e.g., Kübler et al, 2015Kübler et al, , 2020Alonso-Valerdi and Mercado-Garcıa, 2019; or for motor imagery based BCIs, e.g., Lyu et al, 2023). Additionally, guidelines of BCI training protocols have been suggested to incorporate human factors into the BCI settings (Mason and Birch, 2003;Botte-Lecocq et al, 2014;Jeunet et al, 2018).…”
Section: The Human User In Bci Researchmentioning
confidence: 99%
“…This hypothesis and theory paper aimed at raising awareness for including the user’s language and cultural differences as human factors in BCI research. As explained in the previous sections, an interdisciplinary, theory-driven exploration of linguistic and cultural factors and their relevance to design and engineering aspects has not yet been established as a fundamental part of a user-centered BCI approach (for discussion, see, e.g., Kübler et al, 2015 and recent trends e.g., Gena et al, 2023 ). Therefore, future BCI applications should particularly draw attention to linguistic and cultural aspects when designed to include various users.…”
Section: Discussionmentioning
confidence: 99%
“…2020 ). Thus, a notable translational gap remains, despite the fact that BCIs have long been proven feasible under laboratory conditions ( Kübler, 2013 ; Kübler et al, 2015 ; Nijboer, 2015 ). The user-centered approach to BCI design has been adapted to evaluate BCI operation in a multimodal way ( Zickler et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%